Thermostable L2 lipase: enzyme properties and rational design - Raja Abdul Rahman, Raja Noor Zaliha (2012)
Thennostable lipase L2 was originally produced extracellularly by thermophilic Bacillus sp. L2, isolated from a hot spring in Perak, Malaysia. The recombinant L2 lipase has been expressed in Escherichia coli system and later purified by using affinity chromatography. The optimum pH and temperature were 9.0 and 70°C, respectively. The structure of L2 lipase was successfully elucidated. To understand the function of amino acid residue at lipase N-terminal end, rational design was conducted by substitution of the second amino acid in L2 lipase. Result showed that the N-terminal residues of L2 lipase actually play a very important role of maintaining the integrity of the protein.